La Enfermedad Periodontal como Factor de Riesgo para Nacimiento Pretérmino - Maita Veliz, Luis Vidal (2003)
The purpose of this investigation was to determine if periodontal disease in pregnants women is a risk factor to preterm births. For this study a periodontal exam was performed on all one- hundred twenty patients who were divided in two groups: one named cases with sixty preterm postpartum patients and the other one named control with sixty term pregnant who assits to the Hospital Nacional Docente Madre-Niño "San Bartolomé" in the year 2001. The were significant differences between the two group in two aspects. Clinically, the cases group had worse periodontal disease then the control group. Finally, it was determined that periodontal disease during pregnancy is an important risk factor.